A Model Proposal on the Use of Creative Tourism Experiences in Congress Tourism and the Congress Marketing Mix - Özen Kırant Yozcu; Orhan İçöz (PASOS Revista de Turismo y Patrimonio Cultural, 2010)
Congress tourism has a great importance for the extension of the tourism season, enhancement of employment opportunities and tourism revenues, promotion and efficient use of the facilities in the area. Creative Tourism provides an authentic feel for a local culture through informal, hands-on workshops and creative experiences. Ensuring that the attendants of congress tourism take part in creative tourism activities may be an example of the synergy to be achieved by including creative tourism in thecongress marketing mix. In this study the tourism marketing mix, programming, packaging, partnership, people, product, price, promotion, place, are adapted for congress tourism and a model which illustrates how to use the creative tourism experiences and activities within the marketing mix is proposed.